Improving Farmers' Adaptive Coping in the Post-Covid 19 Period: Meningkatkan Koping Adaptif Petani di Masa Pasca COVID-19 - Enggal Hadi Kurniyawan; Erti Ikhtiarini Dewi; Emi Wuri Wuryaningsih; Fitrio Deviantony; Yeni Fitria (KHD Production, 2023)
The conditions of the COVID-19 pandemic have resulted in feelings of anxiety, pressure, and stress on farmers. Anxiety about living during a pandemic can make farmers feel pressured; this can become a stressor for farmers. Community service activities are carried out to improve Farmers' Adaptive Coping in the Post-Covid 19 Period. Participants in this community service were sugar cane farmers, totaling 30 people. This farming community health education was carried out at the Gucialit Village Hall, Lumajang Regency. Counseling on improving Farmers' Adaptive Coping was conducted for 60 minutes using leaflets, x-banners, and banners as media. Submission of material to sugar cane farmers using the lecture method is carried out for 30 minutes, followed by discussion and question and answer for 30 minutes. The material delivered to sugar cane farmers is a Mental Health Media Kit from the Ministry of Health of the Republic of Indonesia. The health education evaluation results show that farmers can understand and carry out several activities to deal with stress. Health education to farmers about mental health is expected to continue to be carried out to improve farmers' adaptive coping in dealing with stress.